In Pursuit of ‘Twin Toleration’: Democracy and Church–State Relations in Serbia and Montenegro - Veković, Marko (Occasional papers on religion in Eastern Europe, 2019)
This paper explores the relationship between church and state in Serbia and Montenegro by examining the development of ‘twin toleration’. In particular, it aims to explain why there is still no ‘twin toleration’ in these states, and why it is important to impose such institutional arrangement in church-state relations. The ‘Twin toleration’ concept suggests that institutional arrangements between the state and religious communities in a democratic society should be based on mutual autonomy, in which the state should not interfere in the matters of religious communities, and vice versa. However, since the fall of communism and resurgence of religion, both the Serbian and Montenegrin states have tended to have close relations with the dominant religious communities in order to achieve their narrow political interests. On the other side, religious communities often interfere in political issues. Such a situation does not contribute to the further development of democracy in these countries. In this paper I employ content analysis in order to investigate constitutions and specific laws on religious communities, if any, in the states mentioned above. Besides its theoretical perspective, aim of this paper is to offer practical suggestions on how to rearrange church-state relations in Serbia and Montenegro in order to make these countries more democratic.